Independence of Judges as Immanent Quality of Criminal Justice and Its Severe Problem - Tarasov, A.A.; Gizatullin, I.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ I͡U︡ridicheskie nauki, 2018)
Independence of judges is an objectively necessary condition for the existence of judicial power and justice in the state, it presupposes the freedom of every judge in choosing a legal position on the issue that he resolves, both from the will of the parties to litigation and from any external influence. External to the judge are not only the impact of the parties in the case under consideration or representatives of non-judiciary or court leadership, but also the corporate impact of the judiciary community or mental attachment to the corporate traditions of the professional communities to which the judge previously belonged. Exposure to all these types of outside influence for the judge constitute an equal threat to his independence and to the justice sent to him. No less threat to justice and objective interests of society is the flip side of judicial independence - judicial arbitrariness. The optimal state approach in ensuring the independence of judges implies a balance between the two extremes - judicial dependence on someone else's opinion and judicial arbitrariness. In modern Russian legislation, the «independence of judges» is defined as the principle of all types of legal proceedings, with the allocation of a special article with this title to all procedural codes. In the laws of the judicial reform of the XIX century, the phrase «independence of judges» is not used at all, although the creation of a truly independent court in conditions of absolute monarchy is recognized as the main achievement of this reform. The authors emphasize on the example of criminal justice that the independence of judges is not ensured at all by its special legislative fixation or elevation in the principles of the process, not by repeated repetition of these words in different legal regulations and even more - not by appeals to specific judges to be independent. Independence of judges can be ensured only by the creation of reliable organizational and procedural mechanisms for its implementation, some of which are analyzed in the article. Among them - the expansion of adversarial principles in the use of special knowledge in the criminal investigation of criminal cases, the introduction of elements of the judicial investigation into the institution of special order of the decision of the court decision with the consent of the accused with the charge, the procedural significance of the reasons for the refusal of the public prosecutor from the prosecution, and others.